Analisis Risiko Pasokan Daging Sapi dalam Kondisi Pandemi COVID-19 (Studi Kasus PD. Rumah Potong Hewan Surya Kecamatan Semampir, Kota Surabaya) (Risk Analysis of Beef Supply in Pandemi Conditions of COVID-19 (Case Study of PD. Slaughterhouse Surya in Semampir District, Surabaya City) - Meilina, Mutiara Putri; Widayanti, Sri; Tondang, Ika Sari (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
This study aims to identify risks and identify risk management strategies in each business process chain at PD. Surya Slaughterhouse. Data analysis in this study used a descriptive qualitative method with a case study research technique. The analytical tool used in this study was the Failure Mode and Effect Analysis (FMEA) approach. Data collection was carried out through surveys, interviews, and expert questionnaires. The results showed that from 6 business process chains, 26 risk events and 25 risk sources were identified, of which 10 risk sources were prioritized to be addressed first, and 7 of the 12 most appropriate mitigation actions were selected to address the priority risks. Possible mitigation actions include: providing safety stock, operational cost efficiency, sanitation training and health protocols, and strict supervision of work facilities. These findings highlight the vulnerability of the supply chain to pandemic shocks.Keywords: Beef, Risk, Mode and Effect Analysis (FMEA), Risk Mitigation.